2015 IEEE MTT-S International Microwave and RF Conference (IMaRC) 2015
DOI: 10.1109/imarc.2015.7411390
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Integrated Waveguide miniaturization using Slow Wave and Half Mode techniques

Abstract: Here in this paper we present a new miniaturized SIW using two techniques together, the first is the Slow-Wave SIW and the second is the Half-Mode SIW. Combining these two techniques shows that we can miniaturize our SIW with a factor of 70%. Comparing to other published papers we have miniaturized the usual SW-SIW without decreasing the quality factor or increasing losses. Also a model for calculating the effective permittivity of these type of transmission line is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…According to [11,13], the purpose of inserting blind vias inside the SIW is to confine the electric field in the upper layer, thus increasing the effective permittivity and decreasing the cutoff frequency. On the other hand, for a specified periodicity of blind vias, the electric and magnetic fields should be decoupled.…”
Section: Field Distribution and Sw Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [11,13], the purpose of inserting blind vias inside the SIW is to confine the electric field in the upper layer, thus increasing the effective permittivity and decreasing the cutoff frequency. On the other hand, for a specified periodicity of blind vias, the electric and magnetic fields should be decoupled.…”
Section: Field Distribution and Sw Effectmentioning
confidence: 99%
“…Recently, [13] showed that combining the SW with HM techniques would reduce conventional SIW dimensions with a remarkable factor (by 70%) in comparison with original SIW, thus a higher miniaturization factor would be achieved. However, only scattering parameters were presented in [13] in order to demonstrate the HM-SW-SIW concept.…”
Section: Introductionmentioning
confidence: 99%